Morfometria geométrica de melipona mandacaia smith, 1863 (hymenoptera, apidae, meliponini) em três localidades - Rodrigues, Francimária (2018)
Knowing the structure of bees‟ populations helps to understand its distribution as well their responses to the environmental variations. With the objective of understanding the effects of the environment factors on the morphological variation, the morphometric answers of Melipona mandacaia in three sites of natural occurrence. In the first moment, the morphological diversity between the sites was verified, as well as the variation during two years (September 2014 to March 2016). Ten individuals from each of the ten colonies in Petrolina (PE), ten in Moreilândia (PE) and ten in São Raimundo Nonato (PI) were collected every 60 days. In the second moment, the morphological response to the change of environment was evaluated. For this, colonies of each meliponary (of the three sites mentioned) were simultaneously transferred to the Serra da Capivara National Park in São Raimundo Nonato-PI (experimental colonies), while others remained in their place of origin (witnessing colonies). In this experiment, that lasted from May to August 2016, ten individuals were collected on the first experimental day and ten individuals 90 days after the transference. The analyses were made using techniques of geometric morphometry on the right anterior wings of the bees. The results suggested divergence within the populations of M. mandacaia during the studied period. The greatest morphological divergence was observed among the populations of São Raimundo Nonato (PI) and Moreilândia (PE), and the smaller divergence occurred between São Raimundo Nonato (PI) and Petrolina (PE). The Mantel test did not show significant correlation between the matrices of shape, size, altitude and geographic distance (P> 0.05) in all evaluated locations. In the grouping of UPGMA the isolation of the population of Moreilândia (PE) was observed, attributed by the landscape and climatic variation of the region inherent to the characteristics of its surroundings. When the populations were evaluated individually, concerning the collection periods, there was a statistically significant variation between the localities and between the dry and rainy periods, in the same locality, suggesting that there is an influence of the environmental component on the wings‟ morphology. In relation to the morphometric response to the change of environment of the three populations studied, there was a significant morphological divergence when considering the distances of Mahalanobis and Procrustes (P <0.0001). This confirmed that the bees displaced to Serra da Capivara National Park (PI), at the end of the experiment, had greater morphological variation than those that remained at their place of origin. The results suggest that the origin of the colony was mainly responsible for the variation in wing shape, but it was influenced by environmental and climatic factors